2021
DOI: 10.1186/s12884-021-03642-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health care utilization and the obstetric outcomes of undocumented women in Finland – a retrospective register-based study

Abstract: Background Undocumented pregnant women constitute a vulnerable group of people who lack equal access to pregnancy care. Previous research has shown that undocumented migrants encounter difficulties in accessing health services, the onset of prenatal care is delayed, and women have an increased risk for infectious diseases. The aim of this study was to describe the use of maternal health care services and the obstetric outcomes of undocumented women in Helsinki, capital city of Finland, in addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
(35 reference statements)
1
21
0
3
Order By: Relevance
“…In the current study, a total of 46.5% of the women came late for their first antenatal visit (i.e. after the first trimester), fewer than in Denmark (52.6%) and Finland (61%) [ 34 , 35 ]. Late presentation was particularly the case for women from countries outside the Africa and Middle East regions, who also had short stays in Norway.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the current study, a total of 46.5% of the women came late for their first antenatal visit (i.e. after the first trimester), fewer than in Denmark (52.6%) and Finland (61%) [ 34 , 35 ]. Late presentation was particularly the case for women from countries outside the Africa and Middle East regions, who also had short stays in Norway.…”
Section: Discussionmentioning
confidence: 82%
“…Our findings of the provision of substandard care should be seen in relation to the challenges of providing care to a marginalized group affected by structural vulnerabilities, on the one hand, and the NGO clinics’ limited and voluntary resources, on the other [ 18 ]. Studies from other Nordic countries show that women only attending NGO clinics, as well as those being referred to public primary care, had a low number of antenatal visits [ 34 , 35 ]. A study from Sweden, found that fear, along with practical and psychosocial factors were barriers to accessing health care for undocumented migrants even when being entitled to public primary care [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that three out of five studies that recruited pregnant migrant women included refugees or undocumented migrants, which are also factors that increase the risk for HIV. 38 , 39 , 40 Two of these three studies reported high HIV prevalence ratios by a large margin (OR of 95·52 and 62·28), likely due to the types of migrants they included, i.e. refugees and undocumented migrants.…”
Section: Discussionmentioning
confidence: 99%
“…As not all women use this option, for instance because they are unaware of the right to shelter or fear deportation, the 319 women in our study probably represent an underestimation of the number of undocumented women giving birth in The Netherlands. Compared to different European populations, poor perinatal health outcomes have been reported in undocumented migrants [ 37 , 38 , 39 ]. Although few studies have compared perinatal outcomes between documented and undocumented migrants, the intersection of a precarious legal status, jeopardized access to healthcare and systemic and social exclusion likely renders undocumented migrants a particularly vulnerable group of pregnant women in ASCs [ 3 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to different European populations, poor perinatal health outcomes have been reported in undocumented migrants [ 37 , 38 , 39 ]. Although few studies have compared perinatal outcomes between documented and undocumented migrants, the intersection of a precarious legal status, jeopardized access to healthcare and systemic and social exclusion likely renders undocumented migrants a particularly vulnerable group of pregnant women in ASCs [ 3 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%